(untitled) (Olhar de Professor, 2012)
The objective of this study is to develop a refl ection on the concept of the school based on René Lourau’s genealogical studies (1996). Through a theoretical review, a discussion is provided of the dialectical relationships between the universal, unique and particular dimensions of institutions and how they can set higher or lower dynamics. The article points out that institutions are human and historical constructions, consisting of elements that are ideological (ideas), economic (structure and function) and political (intentional human action), and are therefore capable of constructing their own reality and infl uencing social reality.